Coherence properties of highly-excited motional states of a trapped ion - Jarlaud,V; Hrmo,P; Joshi,MK; Thompson,RC (Journal of Physics B: Atomic, Molecular and Optical Physics, 2021)
We present a study of the coherence properties of a variety of motional states of a single ion confined in a Penning ion trap. We demonstrate that the motion of the ion has a coherence time of the order of 1 s, using Ramsey interferometry. We introduce a technique for preparing the ion in an incoherent superposition of highly-excited motional states using a simple modification of optical sideband cooling. Coherent manipulation of these states allows measurements of optical and motional coherence to be carried out. We show that these highly-excited motional state superpositions have long coherence times despite the incoherent preparation of the states. Such states can be useful for sensitive motional dephasing measurements.